Pengaruh Citra Merek, Harga, Dan Promosi Terhadap Keputusan Pembelian Pada Sepatu Merek Skechers (Studi Mahasiswa Kampus Unisma) - Celina Ayunda Salsabilla; Nurhajati Nurhajati; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study, namely, to determine the description of the influence of brand image, price, promotion and purchasing decisions. To find out and analyze the influence of brand image, price, promotion on purchasing decisions. To find out and analyze the impact of brand image on purchasing decisions. To find out and analyze the impact of price on purchasing decisions. To find out and analyze the impact of promotion on purchasing decisions. This study uses a purposive sampling technique which is a sampling technique that requires certain considerations, namely all active unisma students who have purchased Skechers brand shoes obtained 75. The results of this study indicate that brand image, price and promotion have a significant effect on purchasing decisions. brand image has a positive and significant effect on purchasing decisions. Price has a positive and significant effect on purchasing decisions. Promotion has a positive and significant effect on purchasing decisions.Keywords: influence of brand image, price, promotion and purchase decision